The Implementation of Kahoot to Improve Students' Understanding Ability on Integral Materials - Rosidah, Siti; Putra, Harry Dwi; Hendriana, Heris (IKIP Siliwangi, 2024)
The ability to understand mathematics is a basic ability that must be improved because there are still many students who have low understanding abilities. Kahoot learning media can improve students' mathematical understanding abilities according to the material and student characteristics. The purpose of this study is to determine the success of applying Kahoot media in improving the ability to understand mathematics in integer material for junior high school students. The method used in this research is quantitative. The data collection technique comes from the results of a description test of 4 questions regarding students' mathematical understanding abilities in integer material. Quantitative data analysis techniques were processed using descriptive and inferential statistics using Microsoft Excel and SPSS applications. This research was conducted on students at one of the MTs in West Bandung class VII as many as 22 students. The results showed that there was an increase in students' mathematical understanding abilities as indicated by the learning outcomes and student responses after the learning process took place. Students can develop their mathematical understanding skills with the help of this Kahoot media. This increase can be proven by the increase in students' pre-test and post-test results as evidenced by the calculation of the n-gain value. The results of the n-gain calculation show that the increase in students is 0.83 in the high category. This means that the application of kahoot media is successful in increasing students' mathematical understanding of integer material.